Inflammatory Response in the Hippocampus of PS1M146L/APP751SL Mouse Model of Alzheimer’s Disease: Age-Dependent Switch in the Microglial Phenotype from Alternative to Classic. - Jiménez, Sebastián; Baglietto-Vargas, David; Caballero, Cristina; Moreno-González, Inés; Torres, Manuel; Sánchez-Varo, Raquel María; Ruano, Diego; Vizuete, Marisa; Gutiérrez-Pérez, Antonia; Vitorica Ferrández, Javier; Baglietto-Vargas, David (Society for Neuroscience, 2008)
Although the microglial activation is concomitant to the Alzheimer's disease, its precise role (neuroprotection vs neurodegeneration) has not yet been resolved. Here, we show the existence of an age-dependent phenotypic change of microglial activation in the hippocampus of PS1xAPP model, from an alternative activation state with Aβ phagocytic capabilities (at 6 months) to a classic cytotoxic phenotype (expressing TNF-α and related factors) at 18 months of age. This switch was coincident with high levels of soluble Aβ oligomers and a significant pyramidal neurodegeneration. In vitro assays, using astromicroglial cultures, demonstrated that oligomeric Aβ42 and soluble extracts from 18-month-old PS1xAPP hippocampus produced a potent TNF-α induction whereas monomeric Aβ42 and soluble extract from 6- or 18-month-old control and 6-month-old PS1xAPP hippocampi produced no stimulation. This stimulatory effect was avoided by immunodepletion using 6E10 or A11. In conclusion, our results show evidence of a switch in the activated microglia phenotype from alternative, at the beginning of Aβ pathology, to a classical at advanced stage of the disease in this model. This change was induced, at least in part, by the age-dependent accumulation of extracellular soluble Aβ oligomers. Finally, these cytotoxic activated microglial cells could participate in the neuronal lost observed in AD.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/14136?template=romeo
Keywords: Alzheimer, Enfermedad de - Modelos animales; Microglia; Hipocampo (Cerebro); Alzheimer; Transgenic model; Neuroinflammation; Hippocampus; Oligomers; Abeta plaques